2016
DOI: 10.1038/hr.2016.72
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin II type 1 receptor-neprilysin inhibitor LCZ696 blocked aldosterone synthesis in a human adrenocortical cell line

Abstract: A recent clinical study indicated that an angiotensin II (Ang II) type 1 (AT) receptor-neprilysin inhibitor (ARNi) designated LCZ696 (sacubitril/valsartan, as combined sodium complex) was superior to enalapril at reducing the risks of death and hospitalization due to heart failure. Therefore, we investigated the possible mechanisms of the beneficial effect of LCZ696, in which the inhibition of neprilysin enhances atrial natriuretic peptide (NP) or brain NP (ANP or BNP)-evoked signals that can block Ang II/AT r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…As both NPs and RAAS blockers may decrease aldosterone levels, it is not clear to what extent these findings reflect AT 1 ‐receptor blockade or NP facilitation, or both combined. Of note, a recent preclinical report showed that combined neprilysin and AT 1 blockade enhanced the aldosterone suppression effects of ANP and BNP in Ang‐II‐sensitized human adrenocortical cells . Similarly, combined neprilysin and AT 1 blockade more effectively attenuated Ang‐II mediated hypertrophic and fibrotic effects on cardiac and renal cells compared with stand‐alone neprilysin inhibition and AT 1 blockade .…”
Section: Discussionmentioning
confidence: 99%
“…As both NPs and RAAS blockers may decrease aldosterone levels, it is not clear to what extent these findings reflect AT 1 ‐receptor blockade or NP facilitation, or both combined. Of note, a recent preclinical report showed that combined neprilysin and AT 1 blockade enhanced the aldosterone suppression effects of ANP and BNP in Ang‐II‐sensitized human adrenocortical cells . Similarly, combined neprilysin and AT 1 blockade more effectively attenuated Ang‐II mediated hypertrophic and fibrotic effects on cardiac and renal cells compared with stand‐alone neprilysin inhibition and AT 1 blockade .…”
Section: Discussionmentioning
confidence: 99%
“…17 The authors also showed that the natriuretic peptide-mediated suppression of aldosterone synthesis was further augmented by co-administration of LBQ657. 17 Collectively, the authors demonstrated that the combined AT1R antagonism by valsartan and LBQ657 neprilysin inhibition significantly enhanced the natriuretic peptide-mediated signaling effects to suppress Ang II-AT1R-induced aldosterone production in adrenocortical cells, without affecting the expression of aldosterone synthase genes 17 (Figure 1). The results revealed a dual inhibitory action of LCZ696 on the aldosterone cascade as an important drug property and revealed a new aspect of the mechanism of LCZ696-mediated beneficial effects in cardiovascular and renal physiology, thereby contributing an interesting finding to the field of hypertension research.…”
mentioning
confidence: 95%
“…Indeed, in one study, LCZ696 treatment significantly increased the circulating ANP and cGMP concentrations, but did not affect plasma aldosterone concentration compared with placebo in hypertensive patients. 11 Interestingly, Miura et al, 17 as reported in this issue, examined the effects of valsartan, ARB and LBQ657-the active moiety of LCZ696-on aldosterone synthesis in a human adrenocortical cell line (NCI-H295R cells) to investigate the possible mechanisms of the beneficial effects of LCZ696. 17 Although there was no difference in the dissociation from AT1R between valsartan +LBQ657 and valsartan alone, the binding affinity of valsartan+LBQ657 to AT1R was greater than that of valsartan alone in an AT1R-expressing human embryonic kidney cell-based living assay.…”
mentioning
confidence: 96%
See 2 more Smart Citations